Competition Law and Regional Economic Integration : An Analysis of the Southern Mediterranean Countries - Geradin, Damien (Washington, DC: World Bank, 2013)
This study argues that adoption strengthening of a competition law regime is a key component of the regulatory reforms, which are required to allow a market economy in the Mediterranean region. It also argues that the competition rules inserted in the Association Agreements signed between the European Union (EU) and the Mediterranean Partners (MPs) currently fail to provide adequate protection against anticompetitive practices affecting trade between these blocks. Moreover, the competition law regimes adopted by the MPs are generally poorly enforced with the consequence that many domestic anticompetitive practices remain unchallenged. In addition, this study addresses the issue of regulatory convergence between the EU and the MPs in the field of competition law, that is, whether the MPs should align their competition rules on European Community (EC) competition rules. It argues that while such convergence would bring a series of benefits to both the EU and the MPs, it would also involve costs. The study thus argues in favor of a prudent approach whereby the transposition of EC competition rules in the MPs would not be automatic, but would be based on the local circumstances of each MP. One of the primary tasks of the MPs' competition authorities should be to develop a realistic enforcement agenda, which would ensure that the limited resources of these authorities are used in the most effective manner possible. In its final part, this study proposes a series of steps that could be taken by the European Union and the MPs to strengthen competition policy in the Mediterranean region, including proposals for technical assistance in the field of competition law.